Late-onset anti-Yo antibody-positive paraneoplastic cerebellar degeneration: a case report - Zhenyu, Zhang; Man, Guo; Guohui, Zhao; Chenglong, Li; Yong, Ma; Jie, Zhou; Zhibiao, Cai (Frontiers in Surgery, 2026)
Anti-Yo antibody-positive paraneoplastic cerebellar degeneration (PCD) is a rare immune-mediated neurological syndrome associated with malignancy, presenting significant diagnostic and therapeutic challenges. This case describes an elderly female patient who developed delayed-onset subacute cerebellar symptoms three years after ovarian cancer resection, ultimately diagnosed with anti-Yo antibody-positive PCD. Although immunotherapy was administered, the patient's ataxia exhibited only limited improvement, suggesting that PCD may progress to an irreversible pathological stage. This case challenges the conventional understanding that PCD typically precedes tumour detection, offering a new perspective on clinical diagnosis and management due to the three-year interval. This case underscores the importance of considering paraneoplastic etiology in patients with unexplained neurological deficits who have a history of tumor surgery. Maintaining awareness for long-term screening for PCD and early management of primary malignancies alongside immunological interventions is crucial for delaying disease progression.